2020
DOI: 10.1101/2020.07.07.192161
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural and molecular dynamics ofMycobacterium tuberculosismalic enzyme, a potential anti-TB drug target

Abstract: AbstractTuberculosis (TB) is the most lethal bacterial infectious disease worldwide. It is notoriously difficult to treat, requiring a cocktail of antibiotics administered over many months. The dense, waxy outer membrane of the TB-causing agent, Mycobacterium tuberculosis (Mtb), acts as a formidable barrier against uptake of antibiotics. Subsequently, enzymes involved in maintaining the integrity of the Mtb cell wall are promising drug targets. Recent… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Inspection of the solvent accessible surface showed that the ligand's binding site is completely buried into the dimer interface, without evident access to the solvent and distant from the substrate or cofactor binding sites, as described for other MEs [12][13][14][15][16]28,29,31 (Figure 2C). Consequently, local structural adjustments would be required for the ligand to access its binding pocket.…”
Section: ■ Results and Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Inspection of the solvent accessible surface showed that the ligand's binding site is completely buried into the dimer interface, without evident access to the solvent and distant from the substrate or cofactor binding sites, as described for other MEs [12][13][14][15][16]28,29,31 (Figure 2C). Consequently, local structural adjustments would be required for the ligand to access its binding pocket.…”
Section: ■ Results and Discussionmentioning
confidence: 74%
“…Contrary to the majority of the eukaryotic large unit MEs, TcMEc does not have N-nor C-terminal extensions that are known to stabilize the tetrameric form of the enzyme 14,16,28,31 (Figure S1). Further, TcMEc showed an estimated molecular mass equivalent to a dimer in size exclusion chromatography (SEC) experiments (Figure S2), which is in agreement with previous studies.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Mtb lacking MEZ displayed altered cell wall composition and attenuated entry into macrophages (39,40). Mtb lacking PPDK had significantly reduced survival upon BDQ treatment compared to the wild type posing PPDK as an attractive drug target (36).…”
Section: Anaplerotic Node and The Tca Cycle Fluxesmentioning
confidence: 99%